Generalization and maintenance of caregivers' effective instruction delivery following group behavioral skills training. (17th February 2022) - LaBrot, Zachary C.; Kupzyk, Sara; Strong‐Bak, Whitney; Bates‐Brantley, Kayla; Caserta, Abigail
Abstract: Behavioral skills training (BST) is an effective modality to train parents in a variety of behavioral techniques for their children. However, extended wait times for behavioral health services can result in increased severity of children's problem behaviors. Furthermore, there is limited research demonstrating that behavior management techniques trained via BST generalizes beyond the setting in which they were trained. The purpose of this study was to evaluate the effectiveness of group‐based BST to improve three caregivers' use of effective instruction delivery (EID) for three children diagnosed with neurodevelopmental disorders and determine the extent to which effective instructions maintained and generalized to the home. Results indicated that all three caregivers' improved their EDI which resulted in children's improved response to instructions that maintained over time. Furthermore, caregivers' use of EID generalized to the home and maintained over time. Findings, implications, and areas for future research are discussed.